Influence of management practices on the incidence of Systole albipennis Walker in fennel (Foeniculum vulgare Mill.) seeds - THAKRAL, R K KASHYAP, O P CHAUDHARY, K K (Journal of Spices and Aromatic Crops, 1994)
The chalcid wasp Systole albipennis Walker (Hymenoptera : Eurytomidae) was observed as the most important pest of fennel (Foeniculum vulgareMill.) seeds under field conditions in Haryana State, India. Studies on influence of management practices on pest infestation indicated that sowing the crop in December-January resulted in maximum seed infestation (up to 17 per cent) and minimum yields (1.1 q/ha) as against October sown crop which resulted in minimum (4 per cent) seed infestation and higher yields (32 q/ha). Plant population per unit area did not affect wasp infestation, though total yield was significantly affected. The loss of seed weight due to wasp infestation was higher in October sown crop, as seeds from this sowing are well developed and infestation of even a single seed amounts to increased loss of seed weight.